How Marketing Perks Influence Word of Mouth - Lisjak, Monika; Bonezzi, Andrea; Rucker, Derek D. (Journal of Marketing, 2021)
This research illustrates how marketing perks can be leveraged to spur WOM. Specifically, this research introduces a previously overlooked yet practically relevant dimension on which perks differ: “contractuality,” defined as the extent to which consumers perceive a perk to be conditional on specific behaviors and contingencies dictated by a company. Importantly, consumers can perceive the exact same perk as more versus less contractual depending on the way it is conferred, structured, or framed. This research demonstrates that low-contractuality perks can be more effective than high-contractuality perks at fostering WOM in the absence of explicit incentives to do so. In particular, low-contractuality perks are more likely than high-contractuality perks to convey a relational signal that motivates consumers to help the company by sharing WOM. Seven experiments, two of which were conducted in the field, support this hypothesis and illustrate conditions under which the effect attenuates or reverses. On the whole, this work offers insights into how managers might design interventions that foster WOM, and it reveals potential trade-offs of commonly used high-contractuality perks.